Evaluasi karakteristik peserta didik dalam menyelesaikan tes kemampuan literasi matematis dan emotional intellegence - Amalia, Kurnia; Safitri, Saskia Dwi; Faradillah, Ayu; Miatun, Asih (Universitas Muhammadiyah Prof. DR. HAMKA, 2025)
Purpose: This study aims to analyze student characteristics in solving mathematical literacy problems and emotional intelligence tests to address the suboptimal mathematical literacy standards in Indonesia through contextual approaches. Design/methodology/approach: A quantitative survey was conducted involving 280 10th and 11th-grade high school students across three Jakarta schools. Data were analyzed using the Rasch Model, utilizing validated descriptive mathematical literacy tasks and emotional intelligence questionnaires as primary instruments. Findings: Wright Map analysis revealed that gender, grade level, and school location significantly influence outcomes. Male and 10th-grade students demonstrated higher performance (25.6%) compared to female and 11th-grade students (11.58%). Furthermore, Differential Item Functioning (DIF) analysis identified specific item biases favoring certain demographic groups. Practical implications: These findings highlight the necessity for educators and curriculum developers to account for student characteristics when designing assessment tools to ensure evaluative fairness and representativeness in academic settings. Originality/value: This study offers novelty by employing the Rasch Model to simultaneously map the intersection of mathematical literacy and emotional intelligence based on specific demographic variables. Purpose: Penelitian ini bertujuan menganalisis karakteristik siswa dalam menyelesaikan soal literasi matematika dan kecerdasan emosional guna mengatasi rendahnya standar literasi matematika di Indonesia melalui pendekatan kontekstual. Design/methodology/approach: Studi kuantitatif ini melibatkan survei terhadap 280 siswa SMA kelas 10 dan 11 di tiga sekolah Jakarta. Instrumen penelitian terdiri dari soal literasi matematika deskriptif dan kuesioner kecerdasan emosional yang telah divalidasi, dengan analisis data menggunakan pemodelan Rasch. Findings: Analisis Wright Map menunjukkan bahwa gender, tingkatan kelas, dan lokasi sekolah berpengaruh signifikan. Siswa laki-laki dan kelas 10 menunjukkan performa lebih tinggi (25,6%) dibandingkan siswa perempuan dan kelas 11 (11,58%). Selain itu, analisis Differential Item Functioning (DIF) mendeteksi adanya bias butir soal yang menguntungkan kelompok demografis tertentu. Practical implications: Temuan ini menekankan pentingnya bagi pendidik dan pengembang kurikulum untuk mempertimbangkan karakteristik siswa dalam menyusun instrumen evaluasi guna menjamin keadilan dan representativitas penilaian di sekolah. Originality/value: Studi ini memberikan kontribusi unik dengan menerapkan Model Rasch untuk memetakan hubungan antara literasi matematika dan kecerdasan emosional berdasarkan variabel demografis secara simultan.